No Significant Difference in Service Learninng Online - McGorry, Sue Y. (Online Learning, 2012)
Institutions of higher education are realizing the importance of service learning initiatives in developing awareness of students’ civic responsibilities, leadership and management skills, and social responsibility. These skills and responsibilities are the foundation of program outcomes in accredited higher education business programs at undergraduate and graduate levels. In an attempt to meet the needs of the student market, these institutions of higher education are delivering more courses online. This study addresses a comparison of traditional and online delivery of service learning experiences. Results demonstrate no significant difference in outcomes between the online and face-to-face models.